Psuedomyxoma peritonei secondary to adenocarcinoma of the cecum - Hussah Al-Buainain; Yasser Al-Jehani; Khaled Moghazy; Abdulaziz Al-Quorain (Wolters Kluwer Medknow Publications, 2010)
Pseudomyxoma peritonei is a rare progressive disease. Patients commonly present with a picture of acute appendicitis or with increasing abdominal girth. We present a case of a 71 year old man who presented with right iliac fossa pain, fever and vomiting. His abdominal examination revealed right iliac fossa mass which was confirmed radiologically. Diagnostic laparoscopy showed jelly like material along with a right iliac fossa mass. The aspirate was negative for malignancy initially. Due to persistance and progression of his disease he underwent right hemicolectomy. Histopathological diagnosis showed moderately differentiated adenocarcinoma of the cecum Duke's C2.